Local community ecotourism business experiences in Kuala Tahan, Malaysia - Aziz, Azlizam; Ramlan, Mohd Aswad; Tasci, Asli D. A.; Johari, Shazali (Forestry Department Peninsular Malaysia, 2012)
Many ecotourism destinations were developed with the dual purpose of resource conservation and local economic well-being. In order to achieve these noble goals, there is a need to incorporate local community participation in ecotourism activity. The vital justification for such participation can be found in the form of linking the economic benefits and conservation. Interest in such linkage was the premise of the present study which was set in Kuala Tahan (Taman Negara National Park), a well known ecotourism destination in Malaysia. The study was designed to examine the experience of the locals in businesses and how they benefited from their participation in ecotourism activities. A census was conducted in Kuala Tahan in 2010 of 69 locals who were involved in businesses providing services to the ecotourists in the park. Results of the study demonstrate an encouraging business atmosphere in Kuala Tahan, and the locals are optimistic about the future of the area. Several changes in business profiles were identified and compared to a previous survey which was conducted in 1993. Although most of the locals are still operating businesses in a conventional manner, some had explored and are thriving in new ventures. A number of problems which could impede the local business growth were also noted and corrective measures suggested.